2020
DOI: 10.1002/acr.24117
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Measures in Large Vessel Vasculitis: Relationship Between Patient‐, Physician‐, Imaging‐, and Laboratory‐Based Assessments

Abstract: Objective To assess the relationship between measures of disease assessment in patients with large vessel vasculitis. Methods Patients with giant cell arteritis (GCA) or Takayasu arteritis (TAK) were recruited into a prospective, observational cohort. Assessments within the following outcomes were independently recorded: 1) patient‐reported outcomes (Multidimensional Fatigue Inventory, patient global assessment of disease activity [PtGA], Short Form 36 health survey [SF‐36], Brief Illness Perception Questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…A further 42 articles were excluded following fulltext assessment. Eventually, 21 studies were selected for the qualitative analysis (systematic review) [16,17,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Eight studies were included in the meta-analysis since these reports contained sufficient data to either evaluate the accuracy of [18F]FDG-PET/CT for discriminating between active disease and remission during treatment [19,23,25,33] or to evaluate the proportion of patients in which the scan normalized during clinical remission in patients on treatment [17,20,22,36].…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…A further 42 articles were excluded following fulltext assessment. Eventually, 21 studies were selected for the qualitative analysis (systematic review) [16,17,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Eight studies were included in the meta-analysis since these reports contained sufficient data to either evaluate the accuracy of [18F]FDG-PET/CT for discriminating between active disease and remission during treatment [19,23,25,33] or to evaluate the proportion of patients in which the scan normalized during clinical remission in patients on treatment [17,20,22,36].…”
Section: Literature Searchmentioning
confidence: 99%
“…Contrast-enhanced CT was performed in two studies. Four studies from the same centre reported that [18F]FDG-PET/MRI was applied in paediatric patients, whereas the adult patients underwent [18F]FDG-PET/CT [16,21,29,31]. The injected [18F]FDG activity was quite heterogeneous and included both weight-based and fixed activities.…”
Section: Technical Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-one studies (1311 patients with TAK, 308 healthy controls) were identified [ 37 – 57 ], all but one [ 52 ] were observational. Ten studies (559 patients with TAK, 182 healthy controls) were synthesized in meta-analysis [ 37 , 39 – 42 , 45 , 51 , 53 , 55 , 56 ], all of whom reported patients with prevalent disease (rather than newly diagnosed disease) on a variety of treatments (ESM Table S5). Most subjects included in the studies were female.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to cancer and various long‐term conditions (eg, Parkinson disease and liver disease), the MFI has been used in several studies in RA, FMS, AS, primary SS, SLE, antineutrophil cytoplasmic antibody–associated vasculitis (AAV), and large‐vessel vasculitis .…”
Section: Multidimensional Fatigue Inventorymentioning
confidence: 99%